Shaping Foreign Policy in Times of Crisis : The Role of International Law and the State Department Legal Adviser / [electronic resource] - Scharf, Michael P.; Williams, Paul R. (Cambridge : Cambridge University Press, 2010)
Shaping Foreign Policy in Times of Crisis grew out of a series of meetings that the authors convened with all ten of the living former U.S. State Department legal advisers (from the Carter administration to that of George W. Bush). Based on their insider accounts of the role that international law actually played during the major crises on their watch, the book explores whether international law is real law or just a form of politics that policymakers are free to ignore whenever they perceive it to be in their interest to do so. Written in a style that will appeal to the casual reader and serious scholar alike, the book includes a foreword by the Obama administration's State Department legal adviser, Harold Koh; background on the theoretical underpinnings of the compliance debate; an in-depth case study of the treatment of detainees in the war on terror; and a comprehensive glossary of the terms, names, places, and events that are discussed in the book.
Title from publisher's bibliographic system (viewed on 09 Oct 2015).